ANALISIS SEKTOR USAHA KECIL MENENGAH (UKM) TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN BONE PROVINSI SULAWESI SELATAN - abdul rahim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
This study aims to determine the effect of small and medium enterprises (SME) growth on labor absorption, the effect of regional minimum wages level for small and medium enterprises toward employment absorption, as well asthe effect of both SME growth and minimum wages on the employment absorption in Bone Regency South Sulawesi. This research was conducted at the Office of Cooperatives and SMEs as well the Manpower Office of Bone Regency, South Sulawesi. The type of researchis descriptive quantitative. The results indicates that the Adjusted R square value of this model is 0.916, which means that 91.60 percent of variations in the employment absorption could be explained by independent variables in the study, while the remaining 8.40 percent is explained by other factors which arenot included in this study. The value of AdjustedR Squares is above 50 percent and categorized inthe good category. In the other wordthe selection of variables affecting the dependent variable is already very appropriate